Analisis Kelayakan Usaha Es Tebu di Desa Juwet Kecamatan Porong Kabupaten Sidoarjo - Khoirotul Mas’ulah; Joko Priyono (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
Analyzing the revenue and viability of the sugar cane ice company in Juwet Village, Porong District, Sidoarjo Regency is the goal of this study. Six Juwet Village ice cane entrepreneurs who were specifically picked based on predetermined criteria made up the research informants. The entire cost, income, profit, and viability of the business are all included in the analysis approach. According to the research findings, the average profit is IDR 10,797,076, the average revenue is IDR 20,060,000, and the average total cost is IDR 9,262,924. An average R/C ratio value of 2.19 (>1) and an average B/C ratio value of 1.19 (>0) were obtained based on the analysis of three business feasibility factors from six informants of ice sugar cane entrepreneurs in Juwet Village. These values indicate that the business is worth conducting. Aside from that, the average ROI value is 56.35% (>0%), indicating that the Juwet Village, Porong District, Sidoarjo Regency sugar cane ice company is profitable and satisfies the required feasibility standards.